SOMATIC GROWTH OF THE MUDFLAT FIDDLER CRAB Uca rapax (Smith, 1870) (Brachyura: Ocypodidae) FROM TWO SUBTROPICAL MANGROVES IN BRAZIL - da Silva-Castiglioni, D; Negreiros-Fransozo, M L (Ecosistemas y Recursos Agropecuarios, 2014)
The crabs were collected monthly, from April 2001 to March 2002 in the mangroves of Itamambuca and Ubatumirim in Ubatuba, São Paulo, Brazil, using the procedure of catch per unit effort (cpue) during 15 minutes at low tide periods by digging the burrows. The sex and carapace width (mm) were recorded for each crab in a sample of 1 294 crabs in Itamambuca mangrove (667 males and 627 females) and 2 107 crabs in Ubatumirim (1 117 males and 990 females). The somatic growth herein described is based on analysis of frequency distributions in size classes using the von Bertalanffy’s growth model. The growth curves based on the carapace width (mm) of males and females are described respectively by the equations: Wt=23.9[1- e–0.21(t+0.87)] and Wt=23.8[1-e–0.16(t+1.18)] in Itamambuca and Wt=21.3[1-e–0.16(t+1.12)] and Wt=20.4[1-e–0..15(t+1.29)] in Ubatumirim mangrove. The crabs from Itamambuca reached their maximum age in 1 620 days (males) and 1 800 days (females), while those from Ubatumirim, required 1 440 days (males) and 1 560 days (females).